2010
DOI: 10.1088/0004-637x/714/1/840
|View full text |Cite
|
Sign up to set email alerts
|

COSMIC MICROWAVE BACKGROUND POLARIZATION AND TEMPERATURE POWER SPECTRA ESTIMATION USING LINEAR COMBINATION OFWMAP5 YEAR MAPS

Abstract: We estimate CMB polarization and temperature power spectra using WMAP 5-year foreground contaminated maps. The power spectrum is estimated by using a model independent method, which does not utilize directly the diffuse foreground templates nor the detector noise model. The method essentially consists of two steps, (i) removal of diffuse foregrounds contamination by making linear combination of individual maps in harmonic space and (ii) cross-correlation of foreground cleaned maps to minimize detector noise bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Here we confine ourselves to the simple case of one foreground component following rigid frequency scaling and two frequency bands. This computation is useful to determine if the low‐ l bias (Saha et al 2008; Samal et al 2010) also leads to violation of statistical isotropy. We then numerically determine the effect of this bias and residual foregrounds on the alignment of quadrupole and octopole.…”
Section: Analysis Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Here we confine ourselves to the simple case of one foreground component following rigid frequency scaling and two frequency bands. This computation is useful to determine if the low‐ l bias (Saha et al 2008; Samal et al 2010) also leads to violation of statistical isotropy. We then numerically determine the effect of this bias and residual foregrounds on the alignment of quadrupole and octopole.…”
Section: Analysis Methodologymentioning
confidence: 99%
“…In the internal power spectrum estimation (IPSE) procedure (Saha, Jain & Souradeep 2006; Saha et al 2008; Samal et al 2010), the cleaning is performed by a blind procedure without making any explicit model for foregrounds. The foregrounds are removed by adding maps in harmonic space at different frequencies with suitable weights, chosen so as to minimize the foreground power.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier publications Souradeep et al 2006;Saha et al 2008;Samal et al 2010) the authors reported that the multipole-based Internal Linear Combination (ILC) method gives rise to a negative bias in its power spectrum at the low multipoles. The bias appears due to a mere chance correlation between CMB and foregrounds at large angles due to availability of only a small number of modes in the large scales on the sky.…”
Section: Power Spectrummentioning
confidence: 99%
“…One of the most important aspects of the method is that it continues to preserve a CMB signal even if it possesses a non-Gaussian nature which may result due to any possible primordial and/or secondary effects, e.g., CMB weak lensing. A detailed account on several other foreground removal methods may be found in existing literature (Brandt et al 1994;Tegmark & Efstathiou 1996;Bouchet & Gispert 1999;Bennett et al 2003;Tegmark et al 2003 Leach et al 2008;Delabrouille et al 2009;Samal et al 2010;Pietrobon et al 2010). For discussions about searching for non-Gaussianity in foreground-minimized CMB maps we refer to Räth et al (2009), Barreiro et al (2000), Banday et al (2000), Raeth et al (2011), Hou et al (2010, and Bernui & Rebouças (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the analysis of WMAP/CMB data has been mainly made using the whole sky area except for strongly contaminated regions Nolta et al 2009;Larson et al 2011;Saha et al 2006Saha et al , 2008Souradeep et al 2006;Eriksen et al 2007a;Samal et al 2010;Basak & Delabrouille 2012). On the other hand, there has been less studies on the power spectrum measurement on partial regions of the sky (e.g., Eriksen et al 2004b;Hansen et al 2004a,b;Ansari et al 2010;Yoho et al 2011;Chiang & Chen 2012).…”
Section: Introductionmentioning
confidence: 99%